Flexible Turbulence Absorbers for Enhancing the Liquid Flow in Pipelines - Abdulbari, Hayder A.; R. M., Yunus; Ashwin Charles, Benedict (2014)
In the present work, an additive-free new technique for enhancing the flow in pipelines is introduced. Such technique depends on inserting Turbulence Altering Pseudo-Surface, TAPS with certain dimensions inside the pipe (adjacent to the inner wall). Such technique is meant to simulate the viscoelastic behaviour of soluble additives to enhance the flow in pipelines. Liquid circulation system with a testing section divided into four subsections was used to test the drag reduction effect of the new technique. The results showed that almost 60% flow enhancement is achievable when inserting 12 strips with 60 cm length into 0.0381 m diameter pipe.